Exposing Nursing Students to Rural Healthcare Practice: Creating a Rural Simulation Experience - Lori Hendrickx; Becka Foerster; Julie Hansen (Rural Nurse Organization; Binghamton University, 2014)
Background: Continued nursing shortages in rural areas have prompted the call for nursing education programs to prepare nursing students for rural practice. Including curricular content on rural health issues and placing students in rural health care facilities are methods used by some institutions. An additional strategy for preparation of students for rural practice is simulation. Method: This project involved the use of simulated health care facilities in rural communities, incorporating rural concepts into rural simulation scenarios and developing a twenty-two member family tree of rural residents for use in the simulation scenarios. Nursing students participate in rural simulation scenarios throughout the curriculum in lecture and lab settings. Conclusions: Using simulation with rural health experiences provides nursing students the opportunity to experience caring for patients from rural areas while increasing their understanding of health care issues, challenges associated with rural health care and opportunities for rural practice. DOI:  http://dx.doi.org/10.14574/ojrnhc.v14i1.307   Keywords: Simulation, Rural, Scenarios, Nursing Education